University academic trajectories: personal and insitutional aspects in teacher training for professionals - Sayago, Andrea Rossana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Since 2019 a team of researchers from the Catholic University of Salta (Argentina) has been carrying out the research project “Curricular Complementation Cycles and Academic Trajectories in Teaching Careers” in order to understand the impact of the curricular format of the university trajectories of adult students who continue their professional training in the field of teaching. This is a case study with qualitative methodology that seeks to analyze the way in which institutional conditions and proposals favor or hinder the trajectories of students in the cohort 2018 considering personal, institutional and pedagogical factors.